The PalaeoEnvironments and ARchaeological Landscapes (PEARL) project: Recent findings from Neolithic sites in Northern Oman. (14th January 2020) - Parton, Ash; Bretzke, Knut
Abstract : The PalaeoEnvironments and ARchaeological Landscapes (PEARL) research project is a joint German–British project with the principal objective of developing a framework of past human occupation and landscape change in south‐eastern Arabia. Fieldwork during 2018 and 2019 involved the systematic survey and excavation of sites in the Rustaq and Ibri regions of Northern Oman, with the aim of establishing the nature and timing of human occupation and landscape change during the Early Holocene period (c. 10, 000–7, 000 years BP). Further to the findings previously reported, results from recent excavations of the site Hayy al‐Sarh in Rustaq revealed the presence of animal remains, stone and shell beads and stone structures, indicating a large Neolithic settlement with burial areas. In addition, preliminary excavations at a rock shelter site near Ibri have revealed stratified archaeological remains, including a Fasad‐type assemblage. Future fieldwork will further develop archaeological and palaeoenvironmental records to help build a framework for studying cultural and natural developments in Northern Oman.